Organisasi Mahasiswa Tempat Belajar Kepemimpinan atau Ajang Popularitas - Rey Kurnia (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research discusses Student Organizations as a Place to Learn Leadership or a Venue for Popularity by using qualitative research with library studies. The results show that several aspects were found, such as Leadership, Organizational Culture, Existence, Interest, and Soft Skills. Student organizations play an important role in the personal development of students. Organizations not only serve as a platform to carry out campus activities, but also as a learning medium for students to develop leadership, organizational culture, self-existence, interest in organizing, and soft skills. Through organizational activities, students can learn to lead, collaborate, communicate, as well as manage time and responsibilities. Additionally, a good organizational culture can enhance work spirit, solidarity, and the success of the organization. Students' interest in participating in organizations is influenced by internal factors such as the desire to develop themselves and their talents, as well as external factors such as support from the campus environment and friends. However, in practice, student organizations can also become a place to seek existence or popularity, especially when the motivation for organizing is more oriented toward social recognition rather than self-quality development.